COGNITIVE STRATEGIES AND CHALLENGES IN LITERARY TRANSLATION FROM ENGLISH TO UZBEK (Ustozlar uchun, 2025)
The translation of literary texts requires more than linguistic competence; it demands complex cognitive strategies that navigate semantic, cultural, and stylistic nuances. This study examines the cognitive strategies employed and challenges faced by translators working on English literary texts translated into Uzbek. Through qualitative analysis of translator interviews and sample translations, combined with theoretical insights from cognitive linguistics and translation studies, the paper highlights key cognitive processes such as inferencing, problem-solving, and conceptual mapping. The research also outlines the significant challenges arising from linguistic typology differences, cultural gaps, and literary stylistic features. Recommendations for enhancing translator training and dictionary resources to support cognitive translation strategies are presented.